Cybercrime: key issues and debates - Gillespie, Alisdair A. (Routledge, Taylor & Francis Group, 2016)
Cybercrime -- Jurisdiction -- Targeting the technology -- Offences relating to data -- Cyberterrorism and cyberwarfare -- Fraud -- Virtual property -- Hate and harm -- Sexualised content 1 : adult pornography -- Sexual content 2 : child pornography -- Offences against the person